2011
DOI: 10.1177/0016986210397830
|View full text |Cite
|
Sign up to set email alerts
|

Student-Identified Exemplary Teachers: Insights From Talented Teachers

Abstract: What roles do teachers play in the development of talent and in the attitude of students toward school? Research indicates that teacher enthusiasm, feedback, and content knowledge are keys to student motivation, learning, and engagement. Research also reveals the importance of positive and supportive student/teacher relationships. In previous work concerning student attitudes toward school, a handful of teachers emerged, in the eyes of their students, as exemplary. Follow-up study provided insights concerning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 16 publications
2
38
0
2
Order By: Relevance
“…For students, passion was understood as a teacher who is deeply engaged with the content and his or her students. As for teachers, passion was related to being "deeply in-love" with the content he or she has to deliver (Gentry et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For students, passion was understood as a teacher who is deeply engaged with the content and his or her students. As for teachers, passion was related to being "deeply in-love" with the content he or she has to deliver (Gentry et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…An adequate climate also had a positive effect on gifted students' well-being and overall satisfaction with their academic experiences in schools. Gentry, Steenbergen-Hu, and Choi (2011), in a mixedmethods study of student-identified exemplary teachers, found that teachers who had the most valuable competencies had the following characteristics: had a genuine interest in students and built strong relationships with them, set high expectations and had high standards for their students, maintained a good classroom climate and had a good time with their students, and had passion toward their teaching and their students.…”
Section: Successful Teachers Of the Giftedmentioning
confidence: 99%
“…Teachers represent a critical factor. Gentry, Steenbergen-Hu, and Choi (2011) propose some student-identified characteristics of exemplary teachers: passion, high expectations, sense of humour, connected with students, engaging with students in meaningful learning and a willingness to differentiate between individual students. Although the teachers in the programme appeared to possess these characteristics, not all students experienced all lessons as challenging and activating, whereas active learning tasks seems to be a prerequisite for enhancing engagement and higher order learning (Biggs, 2012).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…We reviewed literature and grouped exemplary teaching practices (with a particular emphasis on helping students take the charge of their learning) into six categories including instructional support (e.g., Butler et al, 2005), motivational support (e.g., Turner & Patrick, 2008), instrumental support (e.g., Perry, Hutchinson, & Thauberger, 2007), encouraging independent thinking (e.g., Gentry, Steenbergen-Hu, & Choi, 2011), continuous monitoring and feedback (e.g., Butler, 2002a), and a supportive classroom environment (e.g., Ayres, Sawyer, & Dinham, 2004). While ineffective teachers may also display such competencies (Waldrip & Fisher, 2003), exemplary teaching requires putting these components together to support students' SRL.…”
Section: Methodsmentioning
confidence: 99%